2018
DOI: 10.21873/anticanres.13072
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Enteral Access in Patients with Esophageal Squamous Cell Carcinoma Under Neoadjuvant Therapy

Abstract: Background: Enteral feeding tubes used to manage the nutritional status of esophageal cancer were evaluated regarding their effectiveness in patients receiving neoadjuvant therapy. Patients and Methods: A retrospective study evaluating patients with esophageal squamous cell carcinoma undergoing neoadjuvant therapy between 2001 and 2014 was conducted at a medical center. Hospital patients' records for enteral access (EA) insertion and treatment outcomes were statistically analyzed. Results: Patients with EA at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…They showed that EA was associated with improved nutrition in patients undergoing CRT who initially presented as malnourished. This finding was supported by our previous retrospective study (13). These findings suggest a potential benefit of EA for malnourished EC patients.…”
Section: Discussionsupporting
confidence: 86%
“…They showed that EA was associated with improved nutrition in patients undergoing CRT who initially presented as malnourished. This finding was supported by our previous retrospective study (13). These findings suggest a potential benefit of EA for malnourished EC patients.…”
Section: Discussionsupporting
confidence: 86%
“…The protocol employed in this retrospective study was approved by our local institutional review board and ethics committee. Patients included in the current analysis were the same patients as in our previous report (23), and included all consecutive patients who underwent CRT at Hualien Tzu Chi General Hospital between 2001 and 2014. Patients were confirmed as having 1) IA to IIIC ESCC; 2) completed radiotherapy and two cycles of chemotherapy with cisplatin combined with continuous infusion of fluorouracil for squamous cell carcinoma, prior to surgery.…”
Section: Methodsmentioning
confidence: 99%
“…PEG was routinely administered before treatment in nearly all newly diagnosed EC patients before initiation of neoadjuvant treatment 23 . The comparison of the effectiveness of enteral and non‐enteral access in patients treated with neoadjuvant treatment showed that nutrition was preserved, survival was beneficial, and the level of mucositis was minimized 24 . Appropriate feeding in perioperation can decrease the incidence of infection in operation.…”
Section: Discussionmentioning
confidence: 99%